Mahārāshṭra-Caitanya Gaṇeśa Vāsudeva Jośī, urpha, "Sārvajanika Kākā" yāñcẽ saṅkshipta-caritra - Boravaṇakara, Rāmacandra Gaṇeśa (SAMP early 20th-century Indian books project, 1925)
Biography of Gaṇeśa Vāsudeva Jośī, social worker from Pune, India.